Analysis Group outbreak of trichinosis in adolescents in the Samara region - E. S. Gasilina; S. M. Kitaychik; O. V. Borisova; I. Yu. Bogoyavlenskaya; N. P. Kabanova; I. G. Yamshchikova; N. M. Bochkareva; A. S. Polyaev; M. A. Shcherbinina; O. A. Kireeva (Журнал инфектологии)
Objective. To study the peculiarities of trichinosis on the material of the group flashes.Materials and methods. Described and analyzed outbreak of trichinosis in 14 adolescents aged 13 to 18 years, were hospitalized in pediatric infectious ward of the city of Samara.Results. The source of infection – infected meat badger. The severity of illness depend on the amount of meat eaten, that is, the infectious dose of the pathogen. In severe cases, the incubation period of trichinosis was minimal (7 days), and if less severe – the maximum (from 19,5 to 21 days). Mild course also contributed to the early administration of antiparasitic therapy. Most of the children the disease begins with fever and dyspepsia, half recorded rash.At the height of the disease is predominant myalgias, half of cases – swelling. The peculiarity of the current severe trichinosis were pronounced toxic-allergic syndrome, generalized edema, myalgia and myasthenia gravis, up to a full adinamii, organ destruction: infectious-toxic kidney, cardiomyopathy, fulminant hepatitis, polyserositis with ascites, hydrothorax 3 weekdisease. The temperature in most of the patients wore a doublewavelength character with rises in the disease onset and disease for 2–3 weeks. It noted the duration of the clinical symptoms. The longest was myalgic, half of the patients remained at the time of discharge from the hospital. The features of laboratory parameters (leukocytosis, eosinophilia, ALT, AST, CRP) in various forms of the disease. The diagnosis was confirmed by serology (IgM, Ig G to Trichinella spiralis) in different phases of the disease. All patients received a specific antiparasitic therapy albendazolom secondary therapeutic dosage for 10 days, as well as detoxication, allergen and symptomatic therapy is indicated.Conclusion. Thus, health education among the population and will be a true prevention of trichinosis.